Supported double-perovskite photocatalytic material and application thereof

Through the dual perovskite photocatalytic material supported by copper nanoparticles, the problems of low visible light utilization and poor stability of perovskite photocatalytic materials are solved, and the effect of efficient photocatalytic reduction of CO2 is achieved, and it is used in multiple cycles. The catalytic performance is maintained, the preparation process is simplified, and the cost is reduced.

CN119259121AActive Publication Date: 2025-01-07KUNMING UNIV OF SCI & TECH

Patent Information

Application Number
CN202411395041.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-07
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

In the field of photocatalytics, existing perovskite photocatalytic materials have problems such as low visible light utilization, poor catalyst recycling, complex preparation process and high cost. In particular, the Pb element is harmful to the environment and has poor stability, which affects its application. .

Method used

Using a supported double perovskite photocatalytic material, the copper nanoparticles and double perovskite Cs2NaBiCl6 are ultrasonicly dispersed in a water-anhydrous ethanol mixture, and the temperature is controlled to crystallize, and the mass of copper nanoparticles and double perovskites is prepared. Materials with a ratio of 0.4-0.5:1 inhibit ion migration in metal halide perovskites, enhance charge separation efficiency, and improve catalytic activity.

Benefits of technology

It realizes high-efficiency photocatalytic reduction of CO2 at room temperature, good product selectivity, can generate a single product CO 100%. The material has stable performance in multiple cycles, simple preparation process, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259121A_ABST
    Figure CN119259121A_ABST
Patent Text Reader

Abstract

The invention discloses a supported double perovskite photocatalytic material which is prepared by the following steps: putting copper nanoparticles and double perovskite Cs2NaBiCl6 into a water-absolute ethyl alcohol mixed solution, carrying out ultrasonic dispersion, heating the dispersion solution to 55-65 DEG C, carrying out cooling crystallization at a rate of 1-2 DEG C / min, completing the reaction when the temperature is reduced to 25 DEG C, carrying out solid-liquid separation on the reaction product, and washing and drying the solid, the Cu nanoparticle-loaded double-perovskite photocatalytic material is applied to photocatalytic reduction of CO2, the catalyst has the characteristics of high reduction catalysis efficiency and good selectivity, the performance is stable after repeated cyclic utilization, and the material disclosed by the invention is simple in preparation process, high in efficiency and suitable for large-scale production and market popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a lead-free supported double perovskite photocatalytic material with the performance of photocatalytic reduction of CO2, belonging to the technical field of photocatalytic material preparation. Background Art

[0002] With the acceleration of industrialization, carbon dioxide emissions have aggravated the energy crisis, leading to global warming, frequent extreme climates, and increasingly severe energy crises. The background of using photocatalytic degradation of carbon dioxide is mainly due to global climate change and energy shortage problems. It aims to convert carbon dioxide into valuable chemicals or fuels through solar-driven chemical reactions to achieve dual optimization of energy and environment. With the continuous in-depth research in the field of photocatalysis, various photocatalytic materials have shown relatively excellent performance, but there are still problems such as low visible light utilization, poor catalyst recyclability, complex preparation process and high cost. Therefore, it is urgent to develop a highly efficient and inexpensive photocatalyst.

[0003] Perovskite photocatalytic materials have attracted much attention due to their high light absorption capacity, excellent photoelectric conversion efficiency and good catalytic performance. Perovskite photocatalytic materials usually have high crystal symmetry and structural stability. The composition and structure of perovskite photocatalytic materials can be regulated through a variety of options. By changing the composition, crystal structure or adding doping elements, its absorption wavelength range, band structure, electron-hole separation efficiency, etc. can be adjusted to optimize photoelectric conversion and catalytic performance.

[0004] At present, the most common perovskites involved in carbon dioxide reduction are CsPbBr perovskites. Since they contain Pb elements, they are harmful to the environment. Therefore, it is urgent to explore a clean perovskite. However, as a photocatalytic material, perovskites have problems such as poor stability, easy recombination of photogenerated carriers, and poor product selectivity, which affect the application of perovskites in the field of photocatalysis. Therefore, it is necessary to invent a perovskite photocatalyst with good product selectivity and stability. Summary of the invention

[0005] The present invention provides a supported double perovskite photocatalytic material, wherein the material is prepared by placing copper nanoparticles and double perovskite Cs2NaBiCl6 in a water-anhydrous ethanol mixture (V 水 :V 醇 =1:4), after ultrasonic dispersion, the dispersion is heated to 55-65°C, and then cooled and crystallized at a rate of 1-2°C / min. The reaction is completed when the temperature drops to 25°C, the reaction product is separated into solid and liquid, and the solid is washed and dried to obtain a product, wherein the mass ratio of copper nanoparticles to double perovskite Cs2NaBiCl6 is 0.4-0.5:1.

[0006] The copper nanoparticles are prepared by adding copper acetylacetonate and KCl into a water-anhydrous ethanol mixture (V 水 :V 醇 =1:4), ultrasonically dispersed, the dispersion was evaporated to dryness in an 80-90°C oil bath with stirring, the evaporated powder was placed in a tube furnace, and reacted for 90 minutes at 175-185°C in a N2-H2 mixed atmosphere (N2:H2 volume ratio = 9:1) to obtain a product, wherein the molar ratio of copper acetylacetonate to KCl is 1:1-3.

[0007] The double perovskite Cs2NaBiCl6 can be prepared by conventional methods, such as co-precipitation, hydrothermal method or room temperature grinding method.

[0008] Another object of the present invention is to apply the above-mentioned supported double perovskite photocatalytic material in the photocatalytic reduction of CO2.

[0009] The present invention can effectively inhibit ion migration in metal halide perovskite by loading copper nanoparticles, enhance charge separation, and improve the efficiency of charge collection, thereby improving catalytic activity; the material of the present invention can photocatalytically reduce CO2 at room temperature, has high catalytic efficiency and good selectivity for the reduction of CO2, can achieve 100% generation of a single product CO, and can be recycled multiple times. The material of the present invention has a simple preparation process and high efficiency, and is suitable for large-scale production and market promotion applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] Figure 1 X-ray diffraction patterns of the double perovskite photocatalytic material loaded with Cu nanoparticles and Cs2NaBiCl6 prepared in Examples 1 and 2; Figure 2 This is the TEM spectrum of the double perovskite photocatalytic material loaded with Cu nanoparticles in Example 1; Figure 3 This is the EDX mapping spectrum of the Cu element of the double perovskite photocatalytic material loaded with Cu nanoparticles in Example 1; Figure 4 PL spectra comparison of the double perovskite photocatalytic material loaded with Cu nanoparticles and Cs2NaBiCl6 prepared in Examples 1 and 2; Figure 5 It is a comparison diagram of the UV Vis-IR absorption spectra of the double perovskite photocatalytic material loaded with Cu nanoparticles prepared in Examples 1 and 2 and Cs2NaBiCl6; Figure 6 This is a comparison chart of the photocatalytic reduction of CO2 in a liquid phase system between the double perovskite photocatalytic material loaded with Cu nanoparticles prepared in Example 1 and the double perovskite Cs2NaBiCl6; Figure 7This is a comparison diagram of the photocatalytic reduction of CO2 in a solid phase system between the double perovskite photocatalytic material loaded with Cu nanoparticles prepared in Example 1 and the double perovskite Cs2NaBiCl6; Figure 8 This is a diagram showing the effect of the double perovskite photocatalytic material loaded with Cu nanoparticles prepared in Example 1 after repeated use in a liquid phase system; Fig. 9 This is a diagram showing the effect of the double perovskite photocatalytic material loaded with Cu nanoparticles prepared in Example 1 after repeated use in a solid phase system; Fig.10 This is a comparison diagram of the photocatalytic reduction of CO2 in a liquid phase system between the double perovskite photocatalytic material loaded with Cu nanoparticles and the double perovskite Cs2NaBiCl6 in Example 2; Fig.11 This is a comparison diagram of the photocatalytic reduction of CO2 in a solid phase system between the double perovskite photocatalytic material loaded with Cu nanoparticles and the double perovskite Cs2NaBiCl6 in Example 2; Fig.12 This is a diagram showing the effect of the double perovskite photocatalytic material loaded with Cu nanoparticles after repeated use in a liquid phase system according to Example 2; Fig.13 This is a diagram showing the effect of the double perovskite photocatalytic material loaded with Cu nanoparticles after repeated use in a solid phase system in Example 2. DETAILED DESCRIPTION

[0011] The content of the present invention is further explained by the following examples, but these examples do not limit the protection scope of the present invention. The methods in the embodiments are conventional methods unless otherwise specified, and the reagents used are conventional reagents sold on the market unless otherwise specified; Example 1: Preparation of perovskite photocatalytic material 0.4Cu / Cs2NaBiCl6 loaded with Cu nanoparticles 1. Weigh 1 mmol of copper acetylacetonate and 2 mmol of KCl into a clean small glass bottle, add 5 mL of a mixed solution of water and anhydrous ethanol (water: ethanol = 1:4), and disperse by ultrasonication. The dispersion is slowly evaporated to dryness under stirring in an oil bath at 85°C. The evaporated powder is placed in a tube furnace and reacted at 180°C in a N2-H2 mixed atmosphere (9:1) for 90 minutes to obtain copper nanoparticles. 2. Weigh 2.5mmol NaCl, 5mmol CsCl, and 2.5mmol BiCl3 into a polytetrafluoroethylene-lined reactor, add 35mL concentrated hydrochloric acid, stir for 40min, place the reactor in a 60℃ oven for 4h, separate the solid and liquid of the reaction product, wash the solid with anhydrous ethanol and deionized water twice each, freeze-dry and grind for 3min to obtain double perovskite Cs2NaBiCl6; 3. Place copper nanoparticles and double perovskite Cs2NaBiCl6 in a mixture of water and anhydrous ethanol (water: ethanol = 1:4), where the mass ratio of copper nanoparticles to double perovskite Cs2NaBiCl6 is 0.4:1, and disperse them by ultrasonic dispersion. After heating the dispersion to 60°C, cool and crystallize at a rate of 1°C / min. The reaction is completed when the temperature drops to 25°C. The reaction product is separated from the solid and liquid, and the solid is washed twice with anhydrous ethanol and deionized water respectively, and freeze-dried to obtain the double perovskite photocatalytic material 0.4Cu / Cs2NaBiCl6 loaded with Cu nanoparticles.

[0012] The X-ray diffraction pattern of the catalyst 0.4Cu / Cs2NaBiCl6 is as follows Figure 1 As shown in the figure, it can be seen that the perovskite peak position after loading Cu nanoparticles has only a small shift, and the peak shifts to a low diffraction angle, indicating that the Cu nanoparticles are successfully attached to the gaps in the perovskite, causing the lattice spacing to increase slightly; and no other diffraction peaks appear, indicating that the main structure of the perovskite matrix is ​​retained; TEM of the catalyst Figure 2 The lattice fringes are clear, indicating good crystallinity. The lattice spacing is 0.826nm, which matches the (400) plane of the original perovskite. Figure 3 It can be seen that the various elements are evenly distributed, and the Cu nanoparticles are evenly dispersed inside the perovskite through the above preparation method.

[0013] Example 2: The preparation process of this example is the same as that of Example 1, except that in step 3, the mass ratio of copper nanoparticles to double perovskite Cs2NaBiCl6 is 0.5:1, and a double perovskite photocatalytic material 0.5Cu / Cs2NaBiCl6 loaded with Cu nanoparticles is obtained; the X-ray diffraction pattern of the material is shown in Figure 1 ; The PL spectra comparison of the double perovskite photocatalytic material loaded with Cu nanoparticles prepared in Example 1-2 and Cs2NaBiCl6 are shown in Figure 4 From the figure, it can be seen that compared with the double perovskite Cs2NaBiCl6, the photoluminescence peak of the double perovskite photocatalytic material loaded with Cu nanoparticles is lower, indicating that its photogenerated carriers are not easy to recombine, and the ability to separate photogenerated electrons is better, which is conducive to the photocatalytic reaction.

[0014] The comparison of the UV Vis-IR absorption spectra of the double perovskite photocatalytic material loaded with Cu nanoparticles prepared in Example 1-2 and Cs2NaBiCl6 is shown in Figure 5From the figure, it can be seen that the light absorption effect of the double perovskite photocatalytic material loaded with Cu nanoparticles is better than that of the double perovskite Cs2NaBiCl6; this shows that it can better absorb light energy and apply it to the photocatalytic reaction, improving its utilization rate of light energy, so in theory it can better improve the performance of photocatalytic reduction of CO2.

[0015] Example 3: The double perovskite photocatalytic material loaded with Cu nanoparticles and the double perovskite Cs2NaBiCl6 prepared in Examples 1 and 2 are used as catalysts for photocatalytic reduction of CO2 1. Liquid phase system reaction: 50 mg of catalyst was dispersed in 10 mL of a mixed solution of deionized water and methanol (volume ratio 1:4) under ultrasonic action, and then the dispersed liquid was dropped on a quartz block with a diameter of 5 cm. After drying at 70°C, the quartz block with catalyst was placed in a reactor with 10 mL of a mixed solution of deionized water and methanol at the bottom, CO2 was introduced into the mixed solution, and a 300W full-spectrum xenon lamp was used to irradiate the reactor. CO2 was catalytically reduced under the action of the catalyst, and the gas product was detected by gas chromatography (GC); after use, the quartz block with catalyst was collected, washed twice with anhydrous ethanol and deionized water in turn, dried at 60°C, and then recycled twice according to the above method; 2. Solid-phase system reaction: 50 mg of catalyst was placed on a glass fiber filter in a reactor, and water vapor and CO2 were introduced into the reactor to remove air. After 30 minutes, the reactor was closed, and H2O was used as a reducing agent to photocatalytically reduce CO2 at room temperature under irradiation of a 300 W full-spectrum xenon lamp. The gas products were detected by gas chromatography (GC). After use, the catalyst was collected, washed twice with anhydrous ethanol and deionized water in turn, dried at 60°C, and then recycled twice according to the above method.

[0016] Example 1 The results of the reaction and recycling of the double perovskite photocatalytic material loaded with Cu nanoparticles in the above two systems are shown in Figure 6-9 , from the figure, after 4h illumination, the product of the photocatalytic reduction of CO2 by the copper-loaded catalyst in Example 1 in the liquid phase system is CO, and the selectivity of the CO product reaches 100%, and the yield of CO is 61.3μmol / g, and the copper-loaded catalyst is recycled twice, and the selectivity of the CO product is still 100%, and the yields of CO are 64.8μmol / g and 59.6μmol / g respectively; the yield of CO of the copper-loaded catalyst in the solid phase system reaches 82.1μmol / g, and the selectivity of the CO product reaches 100%, and the copper-loaded catalyst is recycled twice, and the selectivity of the CO product is still 100%, and the yields of CO are 84.6mmol / g and 83.3mmol / g respectively, and the catalytic performance of the catalyst is relatively stable; Example 2 The results of the reaction and recycling of the double perovskite photocatalytic material loaded with Cu nanoparticles in the above two systems are shown in Figure 10-13 , from the figure, after 4h illumination, the product of the photocatalytic reduction of CO2 by the catalyst loaded with copper in Example 2 in the liquid phase system is CO, the selectivity of the CO product reaches 100%, and the yield of CO is 54.8mmol / g; after being recycled twice, the selectivity of the CO product is still 100%, and the yields of CO are 55.2μmol / g and 58.6μmol / g respectively; the CO yield of the catalyst loaded with copper in the solid phase system reaches 48.2μmol / g, and the selectivity of the CO product reaches 100%. After being recycled twice, the selectivity of the CO product is still 100%, and the yields of CO are 50.1mmol / g and 47.1mmol / g respectively, and the catalytic performance of the catalyst is relatively stable; The products of the double perovskite Cs2NaBiCl6 are CO and CH4, and the yield is significantly lower than that of the copper-loaded catalyst of the present invention. The CO yield in the liquid phase system is 20.2 mmol / g•h; the CO yield in the solid phase system is 20.4 mmol / g•h; and it produces CH4, so its selectivity is far inferior to the copper-loaded catalyst.

Claims

1. A supported double perovskite photocatalytic material, characterized in that: Copper nanoparticles and double perovskite Cs2NaBiCl6 are placed in a water-anhydrous ethanol mixture, and after ultrasonic dispersion, the dispersion is heated to 55-65°C, and then cooled and crystallized at a rate of 1-2°C / min. The reaction is completed when the temperature drops to 25°C, and the reaction product is separated into solid and liquid. The solid is washed and dried to obtain a double perovskite photocatalytic material loaded with Cu nanoparticles.

2. The supported double perovskite photocatalytic material according to claim 1, characterized in that: The mass ratio of copper nanoparticles to double perovskite Cs2NaBiCl6 is 0.4-0.5:

1.

3. The supported double perovskite photocatalytic material according to claim 1, characterized in that: The copper nanoparticles are prepared by adding copper acetylacetonate and KCl to a water-anhydrous ethanol mixture, dispersing the mixture by ultrasonication, evaporating the dispersion to dryness in an oil bath at 80-90° C. with stirring, placing the evaporated powder in a tube furnace, and reacting the mixture at 175-185° C. in a N2-H2 mixed atmosphere for 90 minutes.

4. The supported double perovskite photocatalytic material according to claim 1, characterized in that: The water-anhydrous ethanol mixed solution is prepared by mixing water and anhydrous ethanol in a volume ratio of 1:

4.

5. The supported double perovskite photocatalytic material according to claim 1, characterized in that: The volume ratio of N2:H2 in the N2-H2 mixed gas is 9:

1.

6. Use of the supported double perovskite photocatalytic material according to any one of claims 1 to 5 in photocatalytic reduction of CO2.

Citation Information

Patent Citations

  • Preparation and application of perovskite material applied to photocatalytic reduction of carbon dioxide

    CN109759069A

  • Tetra-perovskite photocatalytic material and application thereof

    CN116212904A

  • Functional ligand surface modified perovskite nanocrystalline photocatalyst, preparation method and application of functional ligand surface modified perovskite nanocrystalline photocatalyst in photocatalytic reduction of carbon dioxide

    CN117463401A

  • Preparation method of platinum-based alloy catalyst with small size and high loading capacity

    CN117577864A

Cited By

  • High-entropy perovskite composite photocatalytic material as well as preparation method and application thereof

    CN122141690A

  • First main group metal gradient doped Cs2NaBiCl6 perovskite material and preparation method and application thereof

    CN122625239A

  • Copper-doped Cs2NaBiCl6 photocatalyst, preparation method thereof and application of copper-doped Cs2NaBiCl6 photocatalyst in photocatalytic reduction of carbon dioxide

    CN122644091A

  • Ni-doped Cs2NaBiCl6 photocatalyst, preparation method thereof and application of Ni-doped Cs2NaBiCl6 photocatalyst in photocatalytic reduction of carbon dioxide

    CN122644094A

  • Low-concentration iron-doped Cs2NaBiCl6 material, preparation method and application thereof

    CN122665627A